2021
DOI: 10.1016/j.cub.2021.09.022
|View full text |Cite
|
Sign up to set email alerts
|

SHANK3 conformation regulates direct actin binding and crosstalk with Rap1 signaling

Abstract: Actin-rich cellular protrusions direct versatile biological processes from cancer cell invasion to dendritic spine development. The stability, morphology, and specific biological functions of these protrusions are regulated by crosstalk between three main signaling axes: integrins, actin regulators, and small guanosine triphosphatases (GTPases). SHANK3 is a multifunctional scaffold protein, interacting with several actin-binding proteins and a well-established autism risk gene. Recently, SHANK3 was demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 81 publications
(130 reference statements)
2
17
0
Order By: Relevance
“…The change of Asn52 to Arg in the SPN domain has been designed based on the 3D-structure, with the intention to weaken the affinity of the SPN to the Ank domain. Indeed we have shown before that it truly opens up the SPN − Ank interaction 32 . Upon coexpression of WT and mutant forms of the complete N-terminus with the GFP-tagged SPN domain, only the N52R positive control induced a significant increase in binding of the SPN domain to the N-terminus (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The change of Asn52 to Arg in the SPN domain has been designed based on the 3D-structure, with the intention to weaken the affinity of the SPN to the Ank domain. Indeed we have shown before that it truly opens up the SPN − Ank interaction 32 . Upon coexpression of WT and mutant forms of the complete N-terminus with the GFP-tagged SPN domain, only the N52R positive control induced a significant increase in binding of the SPN domain to the N-terminus (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…7 a). We analysed the P141A mutation, together with two controls for which we were confident that they would disrupt the intramolecular contact between SPN and Ank domains: N52R (see above, and 32 ) and L68P, a patient mutation for which we have shown that it disrupts the folding of the SPN domain 18 , 23 , 33 . We also included, in a separate experiment, a mutant which is not involved in the interface between SPN and Ank: R12C.…”
Section: Resultsmentioning
confidence: 99%
“…Salomaa et al . ( 48 ) demonstrated a role for SHANK3 in the cytoskeletal organization of the PSD by modulation of its active (open) and inactive (closed) conformations ( Fig. 4 A ).…”
Section: Conformational Changes In Four Well-known Scaffold Proteinsmentioning
confidence: 97%
“…SHANK3 appears to act as a master regulator of the PSD by organizing cytoskeletal elements to support synaptic signaling. SHANK3 has several protein-binding domains including, among others, an N-terminal SPN domain that binds RAP1 and actin during integrin signaling, an SH3 domain that binds to AMPA receptor (AMPAR) complexes, and an ANK domain that binds cytoskeletal elements such as α-fodrin ( 48 , 49 , 50 , 51 ). Emerging evidence indicates that SHANK3 regulates the PSD, at least in part, through conformational changes that switch SHANK3 between active and inactive states based on its bound ligand ( 48 , 52 ).…”
Section: Conformational Changes In Four Well-known Scaffold Proteinsmentioning
confidence: 99%
See 1 more Smart Citation